THE SOLIDARITY IN ADDRESSING TERMS OF RJ. PALACIO’S CHILDREN NOVEL ‘WONDER’: A SOCIOLINGUISTIC ANALYSIS - Nur Jannah; Dwijani Ratnadewi (Tell : Teaching of English Language and Literature Journal, 2017)
Physical deficiencies sometimes cause bullying, but there are also many people who have senseof solidarity. â€œWonderâ€ (2012) by RJ. Palacio tells about a boy with this deficiency and thisstudy was meant to analyze the addressing terms used among the characters illustratingsolidarity. The aims of the research were to find kinds of solidarity addressing terms chosen bythe characters; the reason and the kind of situation of using the addressing terms. The dialogueswere framed and foregrounded to collect the data. Wardhaugh (2006) addressing terms andLindenberg et. al. (2006) solidarity behaviour indicators were used as the main theories toanalyze the data. The result revealed that there were four kinds of addressing terms foundmentioning first name, kinship term, nickname, and endearment name used in various butmostly friendly, quarreling and serious situation.